Peran Teknologi Informasi terhadap Profitabilitas : Studi Kasus pada PT. BPR Sulawesi Dana Jaya Cabang Makassar - Muhammadin, Akhmad; Pasorong, Yasstia (Universitas Malahayati, 2023)
This study aims to test whether information technology can affect profitability at PT BPR Sulawesi Dana Jaya Makassar Branch. This type of research is research using a quantitative approach with survey methods. The sample used in this study amounted to 31 employees using a random technique. The data collection method used is by distributing questionnaires. Data processing uses simple regression analysis with the help of SPSS Version 26 software. The results of this study state that information technology has no effect on profitability. This is because information technology in its effect on profitability in a financial institution is a must to increase profits.